PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN PELANGGAN MAXIM DI KOTA BATAM - Strahel Idauli Kristin Marbun; Asron Saputra (LPPM Universitas Putera Batam, 2022)
This study aims to determine the effect of service quality, product quality and promotion on Maxim's customers satisfaction in Batam simultaneously and partially. The sample# in this study were customers' of Maxim, in Batam, Sagulung sub-district and Batam City, totaling 400 respondents with non-probability sample method. The results of the study indicate that service quality, products quality and the promotion have a positive effect on customer satisfaction with the regression equation Y = 5.177 + 0.2481X1 + 0.301X2 + 0.280X3. The contribution of the influence of service quality, product quality and promotion to customer's satisfaction simultaneously is 68.8%, the calculated F value is greater than F tabe or (291.197 > 2.6049) with a significance of 0.000 < 0.05. There is a simultaneous positive and significant effect among service quality, products quality and promotion on customer's satisfaction.